2018
DOI: 10.1053/j.ajkd.2018.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Febuxostat Therapy for Patients With Stage 3 CKD and Asymptomatic Hyperuricemia: A Randomized Trial

Abstract: Registered at the UMIN (University Hospital Medical Information Network) Clinical Trials Registry with study number UMIN000008343.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
220
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 275 publications
(256 citation statements)
references
References 39 publications
13
220
1
5
Order By: Relevance
“…We agree that the overall CV disease results from the FEATHER study were consistent with the CARES trial findings, although the sample size was >10 times smaller than that in the CARES trial and underpowered for that purpose . There was no difference in CV mortality and no data are provided, although the number of CV deaths would be less than the overall CV event rates (4 of 219 in the febuxostat group and 7 of 222 in the placebo group) . These data appear to add minimally to the causal inference regarding the CV impact of febuxostat.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…We agree that the overall CV disease results from the FEATHER study were consistent with the CARES trial findings, although the sample size was >10 times smaller than that in the CARES trial and underpowered for that purpose . There was no difference in CV mortality and no data are provided, although the number of CV deaths would be less than the overall CV event rates (4 of 219 in the febuxostat group and 7 of 222 in the placebo group) . These data appear to add minimally to the causal inference regarding the CV impact of febuxostat.…”
supporting
confidence: 73%
“…We thank Dr. Kuwabara for his interest in our article and for sharing data from the FEATHER study as it relates to the CARES trial . We agree that the overall CV disease results from the FEATHER study were consistent with the CARES trial findings, although the sample size was >10 times smaller than that in the CARES trial and underpowered for that purpose . There was no difference in CV mortality and no data are provided, although the number of CV deaths would be less than the overall CV event rates (4 of 219 in the febuxostat group and 7 of 222 in the placebo group) .…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Several recent studies have examined whether febuxostat therapy can mitigate kidney dysfunction and reduce risk of heart failure in the general clinical population . Against the background of those previous studies showing an effect of febuxostat, the findings of the CARES (Cardiovascular Safety of Febuxostat and Allopurinol in Patients with Gout and Cardiovascular Morbidities) trial demonstrated that febuxostat was not inferior to allopurinol in terms of adverse cardiovascular events, whereas the risks of all‐cause mortality and cardiovascular mortality were higher by febuxostat than allopurinol administration in patients with gout …”
Section: Introductionmentioning
confidence: 99%
“…However, the study has not proven that febuxostat increased all‐cause mortality and CV mortality compared with placebo . My group conducted The Effect of Febuxostat to Prevent a Further Reduction in Renal Function of Patients with Hyperuricemia Who Have Never Had Gout and Are Complicated by Chronic Kidney Disease Stage 3 (FEATHER), a multicenter randomized controlled study , which showed no difference in CV mortality between the febuxostat and placebo groups over 108 weeks . The results suggested that febuxostat itself did not increase CV events and adverse events compared with placebo at week 108 (4 of 219 versus 7 of 222; P = 0.37), and the incidence of gouty arthritis was significantly lower in the febuxostat group (2 of 219 versus 13 of 222; P = 0.007) .…”
mentioning
confidence: 99%